Who defines culturally acceptable health access?: universal rights, healthcare politics and the problems of two Mbya-Guarani communities in the Misiones Province, Argentina - Sy, Anahí (2013)
This paper seeks to analyze the problems and barriers encountered when public policy health programs are implemented within indigenous communities. The initial stumbling block for such programs is precisely the idea of health as a universal right, around which emerges a characterization and stereotype of the indigenous population who are consequently addressed as a homogenized unit subsisting below the poverty line, and marginalized. A result of this is that the  particular ethno-cultural register of such populations fails to be acknowledged and form part of a systematic public health policy. Consequently, health policies become generalized in character, unable to variate and differentiate according to the culturally specific contexts within which health outreach and access is needed. In this sense, based on the results of an ethnographic study carried out in two Mbya-Guarani indigenous communities of Argentina, our study highlights as to how public policies of indigenous health are perceived, their impact value measured, and the meanings which emerge locally about the policy practices implemented. Lastly, our study identifies problems that can be avoided in fulfilling the goals of universal policies and certain questions to consider at the time of policy design and implementation.